2008
DOI: 10.3285/eg.57.1-2.5
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence dating: basics, methods and applications

Abstract: Abstract. Luminescence dating is a tool frequently used for age determination of Quaternary materials such as archaeological artefacts, volcanic deposits and a variety of sediments from different environmental settings. The present paper gives an overview of the physical basics of luminescence dating, the necessary procedures from sampling to age calculation, potential problems that may interfere with correct age calculation as well as procedures to identify and resolve those problems. Finally, a brief summary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(123 citation statements)
references
References 279 publications
(241 reference statements)
2
113
0
8
Order By: Relevance
“…Further details on the OSL basic dating principles can be found in a number of review papers: Preusser et al (2008), Wintle (2008), and Rhodes (2011). Previous studies applying OSL dating techniques in Taiwan revealed that the luminescence properties of quartz are highly variable, with a variety of factors in some cases limiting the suitability for dating purposes.…”
Section: Numerical Datingmentioning
confidence: 99%
“…Further details on the OSL basic dating principles can be found in a number of review papers: Preusser et al (2008), Wintle (2008), and Rhodes (2011). Previous studies applying OSL dating techniques in Taiwan revealed that the luminescence properties of quartz are highly variable, with a variety of factors in some cases limiting the suitability for dating purposes.…”
Section: Numerical Datingmentioning
confidence: 99%
“…The OSL samples were prepared following standard procedures (e.g. Preusser et al, 2008;Hülle et al, 2010).…”
Section: Osl Analysismentioning
confidence: 99%
“…Li et al, 1986;Iwata and Jiao, 1993) are still being used even though they do not comply with modern standards (e.g. Aitken, 1998;Hajdas, 2008;Preusser et al, 2008;Coe, 2010). In most cases, no information on methods, laboratories, sampling sites, sampled material, etc., is provided.…”
Section: Introductionmentioning
confidence: 95%
“…Optically Stimulated Luminescence (OSL) dating utilises a light-sensitive latent signal in quartz and feldspar grains induced by ionising radiation, mainly originating from radioactive decay of K, Th and U and their daughter isotopes (cf. Preusser et al, 2008). During sediment transport the signal is depleted (bleached) by daylight and starts to accumulate after burial, when the grains are sealed from light exposure.…”
Section: Introductionmentioning
confidence: 99%